RECONSTRUCTION OF FARAID LEARNING THROUGH INTERACTIVE EDUCATIONAL GAMES: AN EXPERIMENTAL STUDY ON ISLAMIC HIGHER EDUCATION INSTITUTIONS (PTKI) - Saefudin Zuhri; Sholeh Hidayat; Fadlullah Fadlullah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Theoretical and memorization-based approaches still dominate Faraid Science instruction at PTKI, so students struggle to relate concepts to mathematical and contextual inheritance calculation practices. This research aims to describe learning conditions and teaching material needs, develop teaching materials for Faraid HIWAR Science based on interactive educational games, and analyze their feasibility, practicality, attractiveness, effectiveness, and implications in learning. This research uses the Research and Development (R&D) method with the Dick and Carey model, which is carried out through ten systematic stages, ranging from goal identification to summative evaluation. Data were obtained through observation across several universities, validity tests conducted by three experts, questionnaires administered to lecturers and students, and effectiveness tests using independent-samples t-tests and N-gain analysis. The study’s results showed that the developed teaching materials were deemed highly feasible, with an average validity of 92%. Practicality obtained an average of 88.25%, while attractiveness reached 90.7%. The effectiveness test showed a significant difference between the experimental and control classes (0.024 < 0.05), with the experimental class’s N-gain score of 86.71 (effective) and the control class’s 21.87 (ineffective). Faraid Science teaching materials based on interactive educational games are declared valid, practical, interesting, and effective, and relevant to the learning needs of Faraid Science at PTKI. Its use has positive implications for improving understanding, calculation skills in inheritance, and student motivation for learning.